Modulation of nociception by corticotrigeminal pathway- A narrative review (Mediscope, 2020)
Management of chronic pain is one of the most important reason to which medications are given. Traditional medicines which have been used to relieve pain are having a number of limitations. Therefore, novel therapies for pain treatment are essential. Our nervous system can process any kind of injurious stimuli, which is known as nociception. The mechanism of nociception involves a complex interaction of peripheral and central nervous system structures. Brain or cerebral cortex has its own controlling mechanism for pain perception. Trigeminal nerve is the fifth cranial nerve and it receives pain sensation from oro- and craniofacial region and sends the information up to cortex. Recent investigations demonstrate another important role of cortical neurons in addition to pain perception, that is, corticotrigeminal (cortex to trigeminal) pathway excites neurons in the trigeminal nerve that leads to decrease in the pain response induced by noxious stimuli. Thus, as this mechanism can be induced at early stage of nociception, it may reduce the pain sensation. So, the corticotrigeminal pathway could be a new potential target for pain therapies. This short review revisits the concepts how stimulation of primary somatosensory cortex can be transmitted via corticotrigeminal tract which aim for the inhibitory neurons in spinal trigeminal nucleus caudalis (SpVc) and thus potentially generate a feedforward inhibition, explaining the pain modulatory role of the corticotrigeminal pathway.Mediscope Vol. 7, No. 1: Jan 2020, Page 51-57